Age of blood and adverse outcomes in a maternity population. Issue 11 (15th July 2015) - Patterson, Jillian A.; Irving, David O.; Isbister, James P.; Morris, Jonathan M.; Mayson, Eleni; Roberts, Christine L.; Ford, Jane B.
Abstract : BACKGROUND: In recent times there has been debate around whether longer storage time of blood is associated with increased rates of adverse outcomes after transfusion. It is unclear whether results focused on cardiac or critically ill patients apply to a maternity population. This study investigates whether older blood is associated with increased morbidity and readmission in women undergoing obstetric transfusion. STUDY DESIGN AND METHODS: Women giving birth in hospitals in New South Wales, Australia, between July 2006 and December 2010 were included in the study population if they had received between 1 and 4 red blood cell units during the birth admission. Information on women's characteristics, transfusions, and outcomes were obtained from five routinely collected data sets including blood collection, birth, and hospitalization data. Generalized propensity score methods were used to determine the effect of age of blood on rates of severe morbidity and readmission, independent of confounding factors. RESULTS: Transfusion data were available for 2990 women, with a median age of blood transfused of 20 days (interquartile range, 14‐27 days). There were no differences in the maximum age of blood transfused between women with and without severe morbidity (21 [14‐28] days vs. 22 [15‐30] days) and in women readmitted or not (22 [14‐28] days vs. 22 [16‐30] days). After potential confounding factors were considered, no relationship was found between the age of blood transfused and rates of severe morbidity and readmission. CONCLUSION: Among women receiving low‐volume transfusions during a birth admission, there was no evidence of increased rates of adverse outcomes after transfusion with older blood.